MENINGKATKAN KEMAMPUAN KEAKSARAAN AWAL ANAK USIA 5-6 TAHUN MELALUI MEDIA PAPAN PINTAR - Nurlina Ismawati; Sri Widayati; Lu'lu' Khumairoh (Jurnal Anak Usia Dini Holistik Integratif (AUDHI), 2023)
The introduction of early literacy in early childhood should be done in a fun way. One fun way to improve literacy skills in early childhood is to use smart boards. The smart board is a square area that is used as a medium for pronouncing letter sounds. This study used the type of Classroom Action Research (CAR) and was conducted at the Surabaya State University (UNESA) 1 Labschool Kindergarten with research subjects children in group B2 consisting of 11 children, with 5 boys and 6 girls in the age range 5-6 years. The data collection technique used in this study was observation and documentation, while the data analysis technique used was quantitative descriptive. The results showed that there was an increase in the ability to recognize letters in group B2 TK Labschool Unesa 1. In cycle 1, children's initial literacy skills using smart boards were 63.63%. In cycle 2, the child's initial literacy skills through the smart board media in group B2 at TK Labschool Unesa 1 had reached a percentage of 81.81%, thus this study was successful. Therefore, it can be concluded that the use of smart board media can improve early literacy skills in children with an age range of 5-6 years in group B2 TK Labschool Unesa 1.Keywords - Smart Board Media; Early Literacy Ability; Classroom Action Research